Messenger RNA- Versus Retrovirus-Based Induced Pluripotent Stem Cell Reprogramming Strategies: Analysis of Genomic Integrity. (15th April 2014) - Steichen, Clara; Luce, Eléanor; Maluenda, Jérôme; Tosca, Lucie; Moreno-Gimeno, Inmaculada; Desterke, Christophe; Dianat, Noushin; Goulinet-Mainot, Sylvie; Awan-Toor, Sarah; Burks, Deborah; Marie, Joëlle; Weber, Anne; et al.
Abstract : Differentiation studies indicated that mRNA-derived induced pluripotent stem cells (iPSCs) differentiated efficiently into hepatoblasts and that these cells did not load additional copy number variations during differentiation. The integration-free hepatoblasts that were generated constitute a new tool for the study of diseased hepatocytes derived from patients' iPSCs and their use in the context of stem cell-derived hepatocyte transplantation. Abstract: : The use of synthetic messenger RNAs to generate human induced pluripotent stem cells (iPSCs) is particularly appealing for potential regenerative medicine applications, because it overcomes the common drawbacks of DNA-based or virus-based reprogramming strategies, including transgene integration in particular. We compared the genomic integrity of mRNA-derived iPSCs with that of retrovirus-derived iPSCs generated in strictly comparable conditions, by single-nucleotide polymorphism (SNP) and copy number variation (CNV) analyses. We showed that mRNA-derived iPSCs do not differ significantly from the parental fibroblasts in SNP analysis, whereas retrovirus-derived iPSCs do. We found that the number of CNVs seemed independent of the reprogramming method, instead appearing to be clone-dependent. Furthermore, differentiation studies indicated that mRNA-derived iPSCs differentiated efficiently into hepatoblasts and that these cells did not load additional CNVs during differentiation. The integration-free hepatoblasts that were generated constitute a new tool for the study of diseased hepatocytes derived from patients' iPSCs and their use in the context of stem cell-derived hepatocyte transplantation. Our findings also highlight the need to conduct careful studies on genome integrity for the selection of iPSC lines before using them for further applications.